On the "missing link" between formal organization and informal social structure - Starling David Hunter; Henrik Bentzen; Jan Taug (Journal of Organization Design, 2020)
Over the last 40 years, organizational scholars have repeatedly called for more research to reconcile formalist and social network approaches to the intra-organizational structure. The former has primarily been concerned with the reporting relationship which manifests as the chain of command while research on the informal social structure relegates the reporting relationship to a wide and varied range of instrumental and affective relationships such as advice-seeking, knowledge-sharing, trust, and friendship which span the boundaries that the chain of command defines. In this study, we employ the chain of command distance - the length along the chain of command of a path connecting a pair of organizational actors - as the basis for formulating and testing hypotheses about how the formal organization and the informal social structure influence one another. First, we argue that whereas the formal structure affords only one, often very lengthy, path between any pair of actors, the combination of formal and informal structures results in a greater number of significantly shorter paths between actors. Next, we consider one effect of the formal organization on the informal social structure. In particular, we argue that there is an inverse relationship between the chain of command distance and the likelihood of a social or informal connection forming between a pair of actors. We test our hypotheses with demographic data collected from a public sector provider of health, education, and welfare services in rural Norway.
Keywords: 650; Organization structure; Social structure; Informal structure; Organization design; Formal structure; Social network; Network analysis; Social network analysis; Organizational network analysis; Quadratic assignment procedure